Prolonged effectiveness of coronary artery bypass surgery versus drug-eluting stents in diabetics with multi-vessel disease: An updated systematic review and meta-analysis - Ariyaratne, T.; Ademi, Z.; Yap, C.; Billah, B.; Rosenfeldt, F.; Yan, B.; Reid, Christopher (Elsevier Ireland Ltd, 2014)
© 2014 Elsevier Ireland Ltd. All rights reserved. Background: Currently, the appropriateness of percutaneous coronary intervention (PCI) using drug-eluting stents (DES) versus coronary artery bypass grafting (CABG) for patients with diabetes (DM) and multi-vessel disease (MVD) is uncertain due to limited evidence from few randomised controlled trials (RCTs). We aimed to compare the clinical effectiveness of CABG versus PCI-DES in DM-MVD patients using an evidence-based approach. Methods: A systematic review and meta-analyses were conducted to compare the risk of all-cause mortality, myocardial infarction (MI), repeat revascularisation, cerebrovascular events (CVE), and major adverse cardiac or cerebrovascular events (MACCE). Results: A total of 1,837 and 3,052DM-MVD patientswere pooled fromfour RCTs (FREEDOM, SYNTAX,VA CARDS, and CARDia) and five non-randomised studies. At mean follow-up of 3 years, CABG comparedwith PCI-DES was associated with a lower risk of all-cause mortality and MI in RCTs. By contrast, no significant differences were observed in the mean 3.5-year risk of all-cause mortality and MI in non-randomised trials. However, the risk of repeat revascularisations following PCI-DES compared with CABG was 2.3 (95% CI = 1.8-2.8) and 3.0 (2.3- 4.2)-folds higher in RCTs and non-randomised trials, respectively. Accordingly, the risk of MACCE at 3 years following CABG compared with PCI-DES was lower in both RCTs and non-randomised trials [0.65 (: 0.55-0.77); and 0.77 (0.60-0.98), respectively]. Conclusions: Based on our pooled results, we recommend CABG compared with PCI-DES for patients with DM-MVD. Although non-randomised trials suggest no additional survival-, MI-, and CVE- benefit from CABG over PCI-DES, these results should be interpreted with care.